2019
DOI: 10.1016/j.biotri.2019.100104
|View full text |Cite
|
Sign up to set email alerts
|

Tribofilms on CoCrMo alloys: Understanding the role of the lubricant

Abstract: The tribological activation of a passive metal alloy in an aqueous biological environment have been highlighted by many researchers; better known as bio-tribocorrosion. Tribocorrosion processes, which can be found at a number of metal-based biomedical implant interfaces, can be affected by lubricant species such as proteins, amino acids and salts. To date, researchers have quantified how the presence of organic species and the environment affect the tribological and corrosion process. However, the nature of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 62 publications
1
11
0
Order By: Relevance
“…The presence of sulphur in the form of cobalt sulphide has been observed via XPS and SAED images within the tribofilm on the CoCrMo surface slid in bovine serum by Hesketh et al [41]. Furthermore, the authors have identified Mo-S speciation via XPS in a previous study [8]. The presence of sulphur on the surface and its tendency to reduce volume loss due to mechanical wear have been demonstrated in several studies [78,79].…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…The presence of sulphur in the form of cobalt sulphide has been observed via XPS and SAED images within the tribofilm on the CoCrMo surface slid in bovine serum by Hesketh et al [41]. Furthermore, the authors have identified Mo-S speciation via XPS in a previous study [8]. The presence of sulphur on the surface and its tendency to reduce volume loss due to mechanical wear have been demonstrated in several studies [78,79].…”
Section: Discussionmentioning
confidence: 92%
“…A linear E-I response around zero net current was observed. The slope of measured current as a function of applied potential represents the R p which was calculated using the voltage window of ± 5 mV around zero net current as utilized in the previous studies [8,61]. The obtained R p was converted into a corrosion current density ʹ I corr ʹ (Ampere) using the Stern-Geary formula (Eq.…”
Section: Electrochemical Measurementsmentioning
confidence: 99%
See 3 more Smart Citations